2009
DOI: 10.4314/bcse.v23i2.44963
|View full text |Cite
|
Sign up to set email alerts
|

8-Methoxyneorautenol and radical scavenging flavonoids from Erythrina abyssinica

Abstract: ABSTRACT.ABSTRACT. ABSTRACT. ABSTRACT. A new pterocarpan (named 8-methoxyneorautenol) was isolated from the acetone extract of the root bark of Erythrina abyssinica. In addition, the known isoflavonoid derivatives eryvarin L, erycristagallin and shinpterocarpin were identified for the first time from the roots of this plant. The structures were determined on the basis of spectroscopic evidence. The new compound showed selective antimicrobial activity against Trichophyton mentagrophytes. The acetone extract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…This plant species finds extensive application in traditional medicine and is used in the preparation of health tonics by the Maasai community of East Africa [31,32]. In addition, this plant is shown to be rich in flavonoids, a group of natural products known to be efficacious in the management of NAFLD and other metabolic syndrome conditions [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This plant species finds extensive application in traditional medicine and is used in the preparation of health tonics by the Maasai community of East Africa [31,32]. In addition, this plant is shown to be rich in flavonoids, a group of natural products known to be efficacious in the management of NAFLD and other metabolic syndrome conditions [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fifteen pterocarpan derivatives which possess inhibitory effects on protein tyrosine phosphatase 1B (PTP1B) have been isolated from the stem bark of this plant species [33,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other plant species referred to for use in the treatment of trachoma include: Abrus precatorius L. [35], Calpurnia aurea [36], Dodonaea viscosa Linn. [37], Erythrina abyssinica [38], Erythrina indica [39], Jatropha curcas [40], Primula auriculata [41], and Tinospora smilacina Benth. [35].…”
Section: Ethnobotanical and Traditional Medicine As Drug Leadsmentioning
confidence: 99%
“…Flavonoids, the main constituents present in many plant extracts, act as powerful free radical scavengers [17]. Many studies demonstrated positive correlation between antioxidant activity and phenolic content of plant extracts [18].…”
Section: Discusssionmentioning
confidence: 99%